Chest wall desmoid tumours treated with definitive radiotherapy: a plan comparison of 3D conformal radiotherapy, intensity-modulated radiotherapy and volumetric-modulated arc radiotherapy. Issue 1 (December 2016) - Liu, Jia; Ng, Diana; Lee, James; Stalley, Paul; Hong, Angela
Abstract Purpose Definitive radiotherapy is often used for chest wall desmoid tumours due to size or anatomical location. The delivery of radiotherapy is challenging due to the large size and constraints of normal surrounding structures. We compared the dosimetry of 3D conformal radiotherapy (3DCRT), intensity-modulated radiotherapy (IMRT) and volumetric-modulated arc radiotherapy (VMAT) to evaluate the best treatment option. Methods and materials Ten consecutive patients with inoperable chest wall desmoid tumours (PTV range 416–4549 cm3 ) were selected. For each patient, 3DCRT, IMRT and VMAT plans were generated and the Conformity Index (CI), organ at risk (OAR) doses and monitor unit (MU) were evaluated. The Wilcoxon signed-rank test was used to compare dose delivered to both target and OARs. Results The mean number of fields for 3DCRT and IMRT were 6.3 ± 2.1, 7.2 ± 1.8. The mean number of arcs for VMAT was 3.7 ± 1.1. The mean conformity index of VMAT (0.98 ± 0.14) was similar to that of IMRT (1.03 ± 0.13), both of which were significantly better than 3DCRT (1.35 ± 0.20;p = 0.005). The mean dose to lung was significantly higher for 3DCRT (11.9Gy ± 7.9) compared to IMRT (9.4Gy ± 5.4, p = 0.014) and VMAT (8.9Gy ± 4.5, p = 0.017). For the 3 females, the low dose regions in the ipsilateral breast for VMAT were generally less with VMAT. IMRT plans required 1427 ± 532 MU per fraction which was almost 4-fold higher than 3DCRT (313 ± 112, P = 0.005). Compared to IMRT, VMAT plans required 60 % less MU (570 ± 285, P = 0.005). Conclusions For inoperable chest wall desmoid tumours, VMAT delivered equivalent target coverage when compared to IMRT but required 60 % less MU. Both VMAT and IMRT were superior to 3DCRT in terms of better PTV coverage and sparing of lung tissue.